Sejarah Kebijakan Moneter di Dunia Islam: Periode Umawiyah hingga Turki Utsmani - Sodik, Gugun; Janwari, Yadi; Al-Hakim, Sofian (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2025)
This thesis explores the development of monetary policy in the Islamic world, from the Umayyad Dynasty to the Ottoman Empire. The research aims to analyze the evolution of monetary policies, including the minting and standardization of currency, tax administration, and fiscal systems across various Islamic empires that ruled between the 7th and early 20th centuries. During the Umayyad period, the standardization of dinar and dirham coins played a crucial role in international trade. Tax policies, such as jizyah and kharaj, strengthened the fiscal stability of the state. In the Abbasid era, banking and financial administration saw significant growth, with the establishment of institutions like the Baitul Mal and the implementation of the iqtāʿ system. The Umayyad Caliphate in Spain minted gold dinars, supporting the economy of Al-Andalus and connecting it to the Mediterranean trade networks. Smaller kingdoms, including the Fatimid, Mamluk, Safavid Persia, and Mughal India, each introduced innovations in monetary policy and trade, particularly in the use of gold and silver, as well as fiscal policies to maintain economic stability. The Ottoman Empire, as the last great Islamic power, faced significant challenges from internal economic crises and the influence of European colonial powers. Monetary and fiscal reforms were key in the Ottoman efforts to survive, though ultimately insufficient to prevent the empire's collapse. The research concludes that monetary policy in the Islamic world was historically influenced by internal factors, such as political stability and economic development, and external factors, including international trade relations and colonial threats. These policies played a vital role in maintaining economic stability during various periods of governance, but also highlighted the challenges faced by these empires in adapting to global changes.